2017
DOI: 10.17219/acem/64875
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sTREM-1, IL-6 and IL-13 concentration in bronchoalveolar lavage fluid in asthma and COPD: A preliminary study

Abstract: Background. Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) is a cell-surface receptor presented on neutrophils, macrophages and monocytes. Elevated sTREM-1 levels are a marker of acute microbial infections, and have also been reported in chronic lung diseases. IL-6 and IL-13 are effective markers in distinguishing these diseases. IL-6 has been shown to play an important role in chronic obstructive pulmonary disease (COPD), while IL-13 is described as one of the key mediators of allergic ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…IL-6 and IL-13 are produced by immune cells, fibroblasts and epithelial cells, and relevant studies have shown the ability of IL-6 to induce IL-13 synthesis and secretion [ 26 , 27 , 28 , 56 , 57 ]. Both cytokines have demonstrated a role in bronchial epithelium repair; they have also shown a significant role in lung disease development, such as COPD, asthma and involvement in lung fibrosis [ 27 , 57 , 58 , 59 ]. Our study demonstrated the increased secretion of IL-13 in the bronchial epithelium, with higher expression in the stratified squamosa epithelium group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 and IL-13 are produced by immune cells, fibroblasts and epithelial cells, and relevant studies have shown the ability of IL-6 to induce IL-13 synthesis and secretion [ 26 , 27 , 28 , 56 , 57 ]. Both cytokines have demonstrated a role in bronchial epithelium repair; they have also shown a significant role in lung disease development, such as COPD, asthma and involvement in lung fibrosis [ 27 , 57 , 58 , 59 ]. Our study demonstrated the increased secretion of IL-13 in the bronchial epithelium, with higher expression in the stratified squamosa epithelium group.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is involved in the repair processes of the epithelium, in chronic pulmonary disease development and induction of secretion of IL-13. Meanwhile, IL-13 mainly is associated with allergic asthma induction and has less involvement in chronic processes of the respiratory system [ 59 ]. However, relevant studies have shown increased synthesis and secretion of IL-13 by alveolar macrophages in lungs with fibrotic changes [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flexible bronchoscopies (Olympus BF-1T160bronchoscope, Olympus Corporation, Tokyo, Japan) were performed under local anesthesia (2% lidocaine) after premedication with inhaled salbutamol (400 µg), intramuscular atropine (0.5 mg) and oral midazolam (7.5 mg). Supplemental oxygen was applied during the entire procedure and blood oxygen saturation was monitored with a pulse oximeter (Pulsox DP-8, Konica Minolta Inc., Tokyo, Japan) (Proboszcz et al, 2017). Following macroscopic inspection of the bronchial tree, BAL was performed by wedging the bronchoscope in the bronchi of the middle lobe or the lingula and administering 4 × 50 ml sterile NaCl warmed to 37 °C.…”
Section: Extraction Of Alveolar Macrophages From Copd Patientsmentioning
confidence: 99%
“…Blood, bronchoalveolar lavage fluid (BALF) and the specimens of bronchial mucosa and mediastinal lymph nodes were collected and processed as previously described. 19,20 Human Samples Analyses…”
mentioning
confidence: 99%